Shear bond strength of metallic brackets bonded with four different composite resins - Fábio Lourenço Romano; Lourenço Correr-Sobrinho; Darcy Flávio Nouer; Américo Bortolazzo Correr; Mário Alexandre Coelho Sinhoreti; Maria Beatriz Borges de Araújo Magnani (Universidade Estadual de Campinas, 2016)
The objective of this study was to assess the shear bond strength of metallic brackets with different types of Concise composites and the Adhesive Remnant Index (ARI). Sixty bovine permanent lower incisors were inserted into PVC tubes and divided into four groups (n = 15): Group 1 - Transbond XT (control) composite; Group 2 - Concise restorative composite; Group 3 - Concise diluted restorative composite (Artun and Zachrisson's technique); and Group 4 - Concise Orthodontic composite. After bonding the brackets, the samples were stored in distilled water at 37o C for 24 hours and then submitted to shear strength tests (Instron) at a crosshead speed of 0.5 mm/min. Analysis of variance and Tukey's test (5%) were used for statistically analysing the data regarding the shear bond strength results, whereas Kruskal-Wallis test was used for analysing the ARI scores. The shear bond strength mean values (MPa) for Group 1 (12.13) and Group 2 (12.20) were found to be statistically higher (p < .05) than that for Group 3 (8.20). No statistically significant differences were observed (p > .05) between Groups 1, 2, and 4 (9.86) as well as between Groups 3 and 4. Regarding the ARI evaluation, the majority of the fractures involved the bracket/ composite interface